Factors that influence customer’s purchase intention of organic and healthy food in Kota Bharu / Muhammad Hafizuddin Mat Nawi - Mat Nawi, Muhammad Hafizuddin (2012)
The aim of this study was to examine the factors that influence customer’s purchase intention of organic and healthy food in Kota Bharu. There are five (5) independent variables that been studied, which were health consciousness, the attitude, product info and labeling, food safety concern and perceived value. This study also was conduct to examine the underlying factors that might be influence the customer’s intentions to purchase the organic and healthy food products. Moreover, questionnaire had been used in order to get feedback from respondents. Researcher had distributed 120 questionnaires to Binaraya PKINK staffs, Telekom Malaysia Pengkalan Chepa branch staffs, Teachers from Sekolah Kebangsaan Parang Puting and Sekolah Menengah Kebangsaan Kemumin. The sampling is convenient sampling. The method that been use are simple convenient sampling. The data collected was then tested on its frequency and reliability analysis. The correlation analysis was used to test the hypothesis in this study. The finding on reliability was good and it considers that all dependent are acceptable. The findings of this paper suggest five factors are significant for explaining the factors that influence customer’s purchase intention of organic and healthy food in Kota Bharu. Based from the results obtained in this study, researcher suggests some recommendations like make the further research to get more accurate result in the future. It also recommend that make the organic and healthy food awareness among customer and reducing the price will attract more customer purchase intention of organic and healthy food